Cannibalism In In The Heart of the Sea - Allensia Sarah Levira (Kata Kita: Journal of Language, Literature, and Teaching, 2019)
This study examine the causes and the after effects of cannibalism that the survivors of Essex commit in Ron Howard’s In The Heart of the Sea. The main theory for this study is the theory of human’s life and death instinct by Sigmund Freud and also the theory of survival cannibalism. In collecting the materials of the analysis, the researcher examine the details of the films multiple times to get the footage which later used as proofs to reveals the causes and effects of cannibalism. The findings showed that the unfulfilled basic needs and anxiety are the major causes of cannibalism and also that the guilty feeling and fear of people are the aftermath effects of cannibalism. This shows that the act of consuming human flesh affects their lives throughout their lives until they died of old age. As a result, cannibalism had a big impact, both negative and positive, on the survivors’ lives. Keywords: Cannibalism, Human Instinct, Survival, Anxiety